Delayed Presentation of a Penile Fracture: A Case Report - Yadav, Ashok Kumar; Singh, Sudhir Kumar; Chapagain, Raju; Das, Prem; Osti, Jag Mohan; Neupane, Durga (Journal of BP Koirala Institute of Health Sciences, 2021)
Penile fracture is a urological emergency caused by blunt trauma to an erect penis. We report a case of a 40-year-old male who presented with a complaint of a painful swelling of the penis for 4 days. On examination, a flaccid swollen tender penis with bluish discoloration over the shaft and scrotum was noted. A clinical diagnosis of delayed penile fracture was made which was managed immediately surgically under spinal anesthesia. Ourreport emphasizes that penile fracture is diagnosed solely on a reliable history and clinical examination. It has outstanding outcome despite delayed presentation if treated promptly.